Management practice adoption and productivity of commercial aquaculture farms in selected areas of Bangladesh (Journal of the Bangladesh Agricultural University, 2018)
Adoption of scientific management practice is the pre-condition for increasing productivity in any farm business. This study estimates the level of scientific aquaculture management practice (SAMP) adoption, factor affecting adoption and its relation with productivity. Sixty aquaculture farms were selected from 3 upazilas of Mymensingh district of Bangladesh. Adoption level was measured by following Sengupta (1967) while Tobit regression was used to assess the determinants of adoption level. Polynomial regression was employed to show the relationship among farm size, adoption level and productivity. Result revealed that average SAMP adoption level was 54% where 53% farmers were medium adopter. Training, experience, education and extension service had significant positive effect on level of adoption. Productivity was significantly higher for those farmers who adopted more SAMP. Adoption level, productivity and profitability of small farmers were higher than that of large farmers. The study suggests farmers for adopting scientific management practices in order to increase the aquaculture productivity and profitability.J. Bangladesh Agril. Univ. 16(1): 111-116, April 2018